Naringin Dihydrochalcone Ameliorates Cognitive Deficits and Neuropathology in APP/PS1 Transgenic Mice - Yang, Wenjuan; Zhou, Keyan; Zhou, Yue; An, Yuqian; Hu, Tingting; Lu, Jing; Huang, Shichao; Pei, Gang (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is a multi-factorial neurodegenerative disorder with abnormal accumulation of amyloid-β (Aβ) plaques, neuroinflammation, and impaired neurogenesis. Mounting evidences suggest that single-target drugs have limited effects on clinical treatment and alternative or multiple targets are required. In recent decades, natural compounds and their derivatives have gained increasing attention in AD drug discovery due to their inherently enormous chemical and structural diversity. In this study, we demonstrated that naringin dihydrochalcone (NDC), a widely used dietary sweetener with strong antioxidant activity, improved the cognitive function of transgenic AD mice. Pathologically, NDC attenuated Aβ deposition in AD mouse brain. Furthermore, NDC reduced periplaque activated microglia and astrocytes, indicating the inhibition of neuroinflammation. It also enhanced neurogenesis as investigated by BrdU/NeuN double labelling. Additionally, the inhibition of Aβ level and neuroinflammation by NDC treatment was also observed in an AD cell model or a microglia cell line. Taken together, our study indicated that NDC might be a potential therapeutic agent for the treatment of AD against multiple targets that include Aβ pathology, neuroinflammation, and neurogenesis.